Brugada ECG Sign & Chest Pain Mimicking ST Elevation Myocardial Infarction - Omar Mousa; Haroonur Rashid (University Library System, University of Pittsburgh, 2013)
Background: Management of patients with the brugada ECG sign who have no previous history of syncope is still negotiable. We present a case of a 57 year-old Caucasian lady who presented to the emergency department with substernal chest pain. Results: Her past medical history showed that she had two previous episodes of lightheadedness, but no syncope. She had a family history of sudden death secondary to unknown cause in her aunt at the age of 61. Physical exam was unremarkable except for diaphoresis. Electrocardiography (ECG) showed ST elevation in the right precordial leads (V1-V2) with T inversion, mimicking a STEMI. Emergent cardiac catheterization revealed normal coronary arteries. Echocardiogram was normal. Again, interpretation of ECG revealed a Brugada type 1 pattern, characterized by coved-type, gradually descending ST-T segment, elevated J point of more than 2 mm and T wave inversion. Electrophysiological (EPS) testing with a Sodium channel blocker challenge showed a persistent Brugada type 1 pattern with non-inducible ventricular tachycardia. This patient had Brugada type 1 ECG pattern with no previous history of syncope (asymptomatic). Thus she was considered at low risk of developing a serious arrhythmogenic event in the future. Conclusion: A history of syncope remains the best available predictor for arrhythmogenic events. EPS testing in such patients, to stratify the risk and predict for any future events, is still controversial. It is still unjustified to place an implantable cardioverter-defibrillator in asymptomatic non-inducible individuals with the Brugada pattern. These patients should follow up closely with a cardiologist and be aware of the risk of possible triggers of ventricular arrhythmias.